2006
DOI: 10.1590/s0103-50532006000700011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of platinum(II) complexes from trifluoromethyl phenylenediamine, picoline and N-benzyl ethylenediamine derivatives

Abstract: Este trabalho descreve a síntese e a caracterização de onze novos complexos de platina(II), contendo como ligantes derivados da 1,2-fenilenodiamina, da N-benzil etilenodiamina, e da 2-ou 4-picolina. Os complexos foram preparados em rendimentos satisfatórios pela reação dos ligantes com K 2 [PtCl 4 ]. É descrita também a atividade citotóxica de um dos complexos de platina(II), em sete linhagens de células tumorais de origem humana, que se mostrou muito menos ativo do que a cisplatina.This work describes the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The mixture was allowed to stir a further 30 min at 0 °C, then was allowed to warm to room temperature, and stirred for 6 h. Next, sodium borohydride (5.69 g, 150 mmol) was added in small portions at room temperature, and the mixture was stirred for a further 12 h. The reaction was quenched with a minimum of water until no gas evolved, then the solvent was removed in vacuo. The deep yellow crude mixture was distilled at 110 μm (bp 100–105 °C) to produce 5.94 g of product as a clear light yellow oil (44% yield) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture was allowed to stir a further 30 min at 0 °C, then was allowed to warm to room temperature, and stirred for 6 h. Next, sodium borohydride (5.69 g, 150 mmol) was added in small portions at room temperature, and the mixture was stirred for a further 12 h. The reaction was quenched with a minimum of water until no gas evolved, then the solvent was removed in vacuo. The deep yellow crude mixture was distilled at 110 μm (bp 100–105 °C) to produce 5.94 g of product as a clear light yellow oil (44% yield) …”
Section: Methodsmentioning
confidence: 99%
“…The deep yellow crude mixture was distilled at 110 μm (bp 100−105 °C) to produce 5.94 g of product as a clear light yellow oil (44% yield). 36 Single-Crystal X-ray Diffraction (XRD). Single crystals for structure determination were held on nylon loop mounts with Paratone oil.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…The noticeable activity of the organic ligand could be due to the presence of the piperazinyl moiety. Previous investigation showed that the presence of a strong electron-withdrawing group in the aromatic ring leads to a decrease in the cytotoxic activity of platinum(II) complexes [16].…”
Section: Biological Investigationsmentioning
confidence: 99%
“…Although these complexes were less active than cisplatin, they have showed relevant biological activity against the L1210 leukemic cell lines. de Almeida et al also reported that platinum(II) complexes with ligands derived from 1,2phenylenediamine have potential cytotoxicity [16]. The evaluated compounds were less active in vitro than cisplatin.…”
Section: Introductionmentioning
confidence: 97%
“…Mononuclear and polynuclear platinum complexes with several different N ‐benzyl derivatives as ligands were previously prepared by our group (19–22). Cytotoxicity activities for these complexes were assessed against different tumor cell lines, both cisplatin resistant and cisplatin non‐resistant.…”
Section: Introductionmentioning
confidence: 99%